Characteristics and outcomes of admitted patients infected with SARS-CoV-2 in Uganda. Issue 1 (7th September 2020) - Kirenga, Bruce; Muttamba, Winters; Kayongo, Alex; Nsereko, Christopher; Siddharthan, Trishul; Lusiba, John; Mugenyi, Levicatus; Byanyima, Rosemary K; Worodria, William; Nakwagala, Fred; Nantanda, Rebecca; Kimuli, Ivan; et al.
Abstract : Rationale: Detailed data on the characteristics and outcomes of patients with COVID-19 in sub-Saharan Africa are limited. Objective: We determined the clinical characteristics and treatment outcomes of patients diagnosed with COVID-19 in Uganda. Measurements: As of the 16 May 2020, a total of 203 cases had been confirmed. We report on the first 56 patients; 29 received hydroxychloroquine (HCQ) and 27 did not. Endpoints included admission to intensive care, mechanical ventilation or death during hospitalisation. Main results: The median age was 34.2 years; 67.9% were male; and 14.6% were <18 years. Up 57.1% of the patients were asymptomatic. The most common symptoms were fever (21.4%), cough (19.6%), rhinorrhea (16.1%), headache (12.5%), muscle ache (7.1%) and fatigue (7.1%). Rates of comorbidities were 10.7% (pre-existing hypertension), 10.7% (diabetes) and 7.1% (HIV), Body Mass Index (BMI) of ≥30 36.6%. 37.0% had a blood pressure (BP) of >130/90 mm Hg, and 27.8% had BP of >140/90 mm Hg. Laboratory derangements were leucopenia (10.6%), lymphopenia (11.1%) and thrombocytopenia (26.3%). Abnormal chest X-ray was observed in 14.3%. No patients reached the primary endpoint. Time to clinical recovery was shorter among patients who received HCQ, but this difference did not reach statistical significance. Conclusion: Most of the patients with COVID-19 presented with mild disease and exhibited a clinical trajectory not similar to other countries. Outcomes did not differ by HCQ treatment status in line with other concluded studies on the benefit of using HCQ in the treatment of COVID-19.